The link between emotion comprehension and cognitive perspective taking in theory of mind (ToM): a study of preschool children - Macheta, Krystian; Gut, Arkadiusz; Pons, Francisco (Frontiers in Psychology, 2023)
The study examined the relation between perspective taking embedded in theory of mind (ToM) and emotion comprehension (EC) in young children. Our study involved children from Poland aged 3–6 (N = 99; 54% boys) from public and private kindergartens residing mainly in urban areas, whose parents could mostly be classified as middle class. The children were examined with the Test of Emotion Comprehension (TEC) and three tasks targeting three aspects of ToM: a first-order false belief task, an appearance-reality test, and a mental states opacity task. The results showed similarities in performances between these different measures. However, only the opacity task predicted the emotion comprehension test results (η2 = 0.13). The results indicate that the key element of ToM that explains individual differences in children’s emotion comprehension is the full-blown understanding of perspective taking, namely that having access to an object under one description does not ensure access to that object under all descriptions. In the research, we took also into account the linguistic side of such specific competences as ToM and EC, which allowed us to see the role of language in scaffolding the development of children’s ability to handle such socially fundamental tasks as understanding emotions and epistemic states.